DOES PROBLEM BASED LEARNING IMPROVE STUDENTS' SELF-DIRECTED LEARNING ABILITIES? - Sri Sundari; Fajmei Aisah Rahmawati (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: Self-Directed Learning has recently been given much attention by educational institutions in Indonesia. The Problem Based Learning method requires students to be able to take the initiative to learn, analyse learning needs, formulate learning objectives, identify learning resources, select and implement learning strategies that suit themselves and be able to evaluate their own learning outcomes. Both Problem Based Learning and Non-Problem Based Learning methods are required to produce good Self-Directed Learning for their teaching participants. The purpose of this study is to find out the differences in Self Directed Learning in students who are taught using PBL and Non-PBL methods at the University of Muhammadiyah Yogyakarta.Methods: The research was non-experimental with an analytical observational research design using a cross sectional approach. The sampling technique was stratified random sampling with a total sample of 90 students. Self-Rating Scale for Self-Directedness in Learning (SRSSDL) by Fisher Instruments was used in this study. The data was analysed by using simple linear regression test.Results: The result showed that SRSSDL score (p = 0.035) and GPA score (p = 0.046). The results indicated that there was a difference between the SDL of PBL and Non-PBL students.Conclusion: There is a difference in the ability of SDL (self-directed learning) between the PBL and Non-PBL methods.